Mucin-Type O-Glycosylation in Invertebrates - Erika Staudacher (Molecules, 2015)
O-Glycosylation is one of the most important posttranslational modifications of proteins. It takes part in protein conformation, protein sorting, developmental processes and the modulation of enzymatic activities. In vertebrates, the basics of the biosynthetic pathway of O-glycans are already well understood. However, the regulation of the processes and the molecular aspects of defects, especially in correlation with cancer or developmental abnormalities, are still under investigation. The knowledge of the correlating invertebrate systems and evolutionary aspects of these highly conserved biosynthetic events may help improve the understanding of the regulatory factors of this pathway. Invertebrates display a broad spectrum of glycosylation varieties, providing an enormous potential for glycan modifications which may be used for the design of new pharmaceutically active substances. Here, overviews of the present knowledge of invertebrate mucin-type O-glycan structures and the currently identified enzymes responsible for the biosynthesis of these oligosaccharides are presented, and the few data dealing with functional aspects of O-glycans are summarised.